Approaches to IS strategic planning in public sector organisations - Boyer, Jorge Diaz Padilla (Trinity College (Dublin, Ireland). Trinity Business School, 2007)
The strategic planning of information systems (IS) involves the development of functional-level IS strategies which contain activities and applications to assist an organisation in managing the IS area, executing its business plans and achieving its business goals. Previous research has demonstrated that it is necessary that the IS strategies are strongly synchronised with the overall business strategies. However, not only have these studies been undertaken in the private sector, but due to a large number of organisations with an inadequate synchronisation situation, there is still a need to further understand how to carry out the process, especially in the public sector. Therefore, in order to detail the synchronisation’s nature and recognise the reasons for its accomplishment, an investigation and research question were proposed with the objective of explaining why and how public sector organisations synchronise their business and IS strategies.
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin